2013
DOI: 10.1158/0008-5472.can-12-3000
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Resistance Associated with PARP Hyperactivation

Abstract: Non-small cell lung carcinoma patients are frequently treated with cisplatin (CDDP), most often yielding temporary clinical responses. Here, we show that PARP1 is highly expressed and constitutively hyperactivated in a majority of human CDDP-resistant cancer cells of distinct histologic origin. Cells manifesting elevated intracellular levels of poly(ADP-ribosyl)ated proteins (PAR high ) responded to pharmacologic PARP inhibitors as well as to PARP1-targeting siRNAs by initiating a DNA damage response that tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 48 publications
6
126
2
Order By: Relevance
“…5,16,22,35 Here, we found that this resistance phenotype correlate with gene expression regulation of several Figure 6 Caspase role in cell death elicited by PDIA4 and PDIA6 knockdown and CDDP. R1, R2 and R3 cells were treated only with siRNA PDIA6 for 48 h followed by 2 h of 50 mM caspase inhibitor Z-VAD or Z-LEVD and/or 48 h of 25 mM CDDP treatment.…”
Section: Discussionmentioning
confidence: 68%
“…5,16,22,35 Here, we found that this resistance phenotype correlate with gene expression regulation of several Figure 6 Caspase role in cell death elicited by PDIA4 and PDIA6 knockdown and CDDP. R1, R2 and R3 cells were treated only with siRNA PDIA6 for 48 h followed by 2 h of 50 mM caspase inhibitor Z-VAD or Z-LEVD and/or 48 h of 25 mM CDDP treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Michels and colleagues analyzed several cisplatin-resistant cancer cell lines and found that a subset of these lines overexpress PARP1 and display hyperactivity of PARylation. Furthermore, a positive correlation was observed between the cellular PARylation and the sensitivity to PARP inhibitors (Michels et al, 2013). It should be noted that clinical experience thus far has shown that platinum-sensitive tumors are more likely to respond to PARP inhibitors than are platinumresistant or platinum-refractory diseases (Fong et al, 2010), so the clinical prospect of this observation remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum drugs bind to DNA and the resulting complex induce lesion of DNA molecules, leading to cell death (OlaussenDunant et al, 2006). Therefore, proteins in DNA repair pathways can affect response to platinum drugs and influence the survival of patients (Parsons et al, 2005;OlaussenDunant et al, 2006;Rosell et al, 2007;KamalSoria et al, 2010;Michels et al, 2013).…”
Section: Discussionmentioning
confidence: 99%